Aircraft carrier operations in the Philippines during the Second World War, 1941-1945 - Tan, Ryan Martin A (Animo Repository, 2021)
The Philippines, as a focal battleground in the conflict between militaries of the United States and the Japanese Empire during the Second World War, saw numerous naval campaigns in its waters. The study plans to analyze through the concepts of zeitgeist and naval theory, the importance of these carrier-borne operations, their impact on the events of the Second World War in the Philippines. This is to be done by analyzing the aircraft carrier operations conducted in the Philippines through a discussion of three separate campaigns where aircraft carrier operations were employed throughout the course of the war, namely the 1941-1942 invasion of the Japanese, the Battle for Convoy Hi-71 from 1943-1944 and the airstrikes conducted by the US Navy during the 1944-1945 liberation of the Philippines. By determining how the tactics used by American and Japanese aircraft carrier forces in the Philippines evolved over the course of the war, the effects these operations had on the strategic outcome of the war could thus be determined. The study plans to fully synthesize how the operations in the Philippines became a major factor in the evolution of naval tactics in the 20th century and factored in the victory of the Allied forces in the Philippines.